Fine‐scale genetic structure and flowering output of the seagrass Enhalus acoroides undergoing disturbance - Yu, Shuo; Wu, Yunchao; Serrao, Ester A.; Zhang, Jingping; Jiang, Zhijian; Huang, Chi; Cui, Lijun; Thorhaug, Anitra; Huang, Xiaoping (Ecology and evolution, 2019)
Seagrass are under great stress in the tropical coast of Asia, where Enhalus acoroides is frequently the dominant species with a large food web. Here, we investigate the question of the fine‐scale genetic structure of this ecologically important foundation species, subject to severe anthropogenic disturbance in China. The genetic structure will illuminate potential mechanisms for population dynamics and sustainability, which are critical for preservation of biodiversity and for decision‐making in management and restoration. We evaluated the fine‐scale spatial genetic structure (SGS) and flowering output of E. acoroides, and indirectly estimated the relative importance of sexual versus asexual reproduction for population persistence using spatial autocorrelation analysis. Results reveal high clonal diversity for this species, as predicted from its high sexual reproduction output. The stronger Sp statistic at the ramet‐level compared with genet‐level indicates that clonality increases the SGS pattern for E. acoroides. Significant SGS at the genet‐level may be explained by the aggregated dispersal of seed/pollen cohorts. The estimated gene dispersal variance suggests that dispersal mediated by sexual reproduction is more important than clonal growth in this study area. The ongoing anthropogenic disturbance will negatively affect the mating pattern and the SGS patterns in the future due to massive death of shoots, and less frequency of sexual reproduction. Enhalus acoroides exhibits high clonal diversity, indicating the importance of sexual reproduction for propagation. This also highlights that seed‐based restoration may be adequate in the disturbed meadows. Significant SGS pattern was found at the ramet‐level and the genet‐level. Stronger SGS pattern at the ramet‐level indicated that clonality increases the spatial genetic structure at a fine scale.